2016
DOI: 10.7324/japs.2016.60710
|View full text |Cite
|
Sign up to set email alerts
|

Study the release kinetics of curcumin released from PVA/curcumin composites and its evaluation towards hepatocarcinoma

Abstract: The polymer composites based on Polyvinyl alcohol loaded with different concentrations of commercial curcumin were prepared to be applied forcontrolled release drug delivery system to overcome the growth promotion of tumor cells. The prepared composites were subjected to drug release in aqueous media at room temperature. It was found that the amount of the released curcumin changed according to different pH media and the concentration of the loaded drug onto the polymer carrier. The diffusion coefficient of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 18 publications
(13 reference statements)
2
21
0
Order By: Relevance
“…To understand the distinction between these two peaks, the mechanism of gel formation must be considered. PVA is a long chain flexible polymer with the backbone of carbon with numerous of 1,3‐ cis ‐diol hydroxyl groups . It is believed that mono borate ions, which is obtained from Borax dissociation in the water beside boric acid, are responsible for crosslinking reaction by means of tetrahedral di‐diol complex formation with diol units of PVA chains .…”
Section: Resultsmentioning
confidence: 99%
“…To understand the distinction between these two peaks, the mechanism of gel formation must be considered. PVA is a long chain flexible polymer with the backbone of carbon with numerous of 1,3‐ cis ‐diol hydroxyl groups . It is believed that mono borate ions, which is obtained from Borax dissociation in the water beside boric acid, are responsible for crosslinking reaction by means of tetrahedral di‐diol complex formation with diol units of PVA chains .…”
Section: Resultsmentioning
confidence: 99%
“…Hence most studies have reported on administration of CN encapsulated in CS-NPs via the parenteral route to provide sustained delivery of drug for breast cancer, hepatocarcinoma and tumour cells at pH 5 or above. [33][34][35][36] Some reports on CS-CN-NPs revealed enhanced bioavailability of anticancer and antimalarial drugs in comparison with pure CN but did not show the effect of acidic pH on release of NPs. [37][38][39] In this study, the coating of chitosan nanoparticles with pH sensitive Eudragit polymer was exhaustively studied to overcome the effect of highly acidic environment.…”
mentioning
confidence: 99%
“…High WVTR may cause dryness of the wound, while low WVTR may cause storing of wound exudates which may result in retardation of the wound healing (Xu et al, 2016). The values of the WVTR for normal skin have been reported to be in the range 8.5 g/m 2 /h to 11.6 g/ m 2 /h (Gonzalez et al, 2012). The WVTR values for cur loaded PVA, Cs and PVA/Cs blend are shown in Table 2.…”
Section: Water Vapor Transmission Rate (Wvtr)mentioning
confidence: 99%
“…It is believed to have many biological activities such as antioxidant, anti-inflammatory, and even anticancer effect. Several studies suggest that it might reduce inflammation and pain symptoms resulted from osteoarthritis and rheumatoid arthritis (Weber et al, 2005;Shankar et al, 2012;Fan et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation